(untitled) (Journal of Health Sciences, 2014)
Introduction: Antibiotic options in the treatment of extended spectrum beta-lactamase (ESBL) producing bacteria are very limited. The purpose of this study was to analyze several commonly applied antibiotics in quite various novel combinations for use against ESBL-producing bacteria isolates.Methods: Total of 460 samples of urine, throat and anal swab were collected from volunteers and patients from nursery, primary and secondary schools and from other individuals in the community. Hospital and community isolates comprised of 65% and 35% respectively. The identification and characterization of the isolates were done by standard culturing and in vitro antibiotic sensitivity procedures.Results: The antibiotic combination studies showed that the combination of gentamicin with the other antibiotics had predominantly synergistic effects. The percentage synergistic effect for the combinations of gentamicin/pefloxacin was 69%, gentamicin/[Amoxicillin and clavulanic acid] 72%, gentamicin/ceftriaxone 68%, gentamicin/cefuroxime 81.9%, and gentamicin/ciprofloxacin 80.6%, against the community and hospital derived ESBL producing organisms of both Enterobacteriaceae and Pseudomonas species.Conclusion: Good antimicrobial monitoring exercise and corresponding antimicrobial screening activities should work towards a dynamic approach to generate effective treatment options using combination therapy.